2013
DOI: 10.1128/aem.00525-13
|View full text |Cite
|
Sign up to set email alerts
|

Living Side by Side with a Virus: Characterization of Two Novel Plasmids from Thermococcus prieurii, a Host for the Spindle-Shaped Virus TPV1

Abstract: c Microbial cells often serve as an evolutionary battlefield for different types of mobile genetic elements, such as viruses and plasmids. Here, we describe the isolation and characterization of two new archaeal plasmids which share the host with the spindleshaped Thermococcus prieurii virus 1 (TPV1). The two plasmids, pTP1 and pTP2, were isolated from the hyperthermophilic archaeon Thermococcus prieurii (phylum Euryarchaeota), a resident of a deep-sea hydrothermal vent located at the East Pacific Rise at 2,70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 52 publications
1
27
0
Order By: Relevance
“…For this reason, it has been proposed that the two plasmids be classified into a new plasmid group (190). Consistent with this notion, plasmid tree analysis revealed that pGT5, pTN1, and pTP1, another thermococcal RCR plasmid (191), form one clade, which we propose to denote the pGT5 plasmid family, whereas pTA1 and pAMT11 form another clade (Fig. 11).…”
Section: Genomic Featuressupporting
confidence: 55%
“…For this reason, it has been proposed that the two plasmids be classified into a new plasmid group (190). Consistent with this notion, plasmid tree analysis revealed that pGT5, pTN1, and pTP1, another thermococcal RCR plasmid (191), form one clade, which we propose to denote the pGT5 plasmid family, whereas pTA1 and pAMT11 form another clade (Fig. 11).…”
Section: Genomic Featuressupporting
confidence: 55%
“…and and Table ). These proteins are also encoded by MGEs from other families in Thermococcales, such as the plasmid pTN3 (Gaudin et al ., ), the virus TPV1 (Gorlas et al ., ) and the integrated plasmid TKV1 (Fukui et al ., ) and by MGEs from other archaeal lineages (Krupovič et al ., ; Krupovic et al ., ). Moreover, one or several genes encoding MCM proteins are present in all archaeal genomes and correspond to chromosomal replicative helicases (Raymann et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, module 10 includes two small rolling-circle plasmids, Archaeoglobus profundus plasmid pGS5 (71) and Thermococcus prieurii plasmid pTP2 (72), which connect to members of the genus Alphapleolipovirus (Halorubrum pleomorphic viruses 1, 2, and 6) through an RCRE. The latter protein is also shared with the putative provirus MVV, which is related to Turriviridae from module 6, as well as with the Sulfolobus monocaudavirus 2 (SMV2) from module 9.…”
Section: Figmentioning
confidence: 99%